2011
DOI: 10.1007/s11060-011-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of vascular endothelial growth factor-producing cells in clinical radiation necrosis of the brain: pathological consideration of their potential roles

Abstract: The cell type and localization of vascular endothelial growth factor (VEGF)-producing cells in human radiation necrosis (RN) are investigated from a histopathological and immunohistochemical standpoint using clinical specimens. Eighteen surgical specimens of symptomatic RN in the brain were retrospectively reviewed. These cases included different original histological tumor types and were treated with different radiation modalities. Histological analyses were performed using hematoxylin and eosin (H&E) stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 34 publications
(44 reference statements)
5
101
0
1
Order By: Relevance
“…There is no obvious histological difference between RN and pseudoprogression, with necrosis being the central feature of both [21,22]. In addition, RN is also characterized by marked enhancement in the tumor bed but without actual tumor, like pseudoprogression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is no obvious histological difference between RN and pseudoprogression, with necrosis being the central feature of both [21,22]. In addition, RN is also characterized by marked enhancement in the tumor bed but without actual tumor, like pseudoprogression.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, RN often shows severe symptoms and occurs at least 6 months following radiotherapy, can be long lasting, and improves only with intensive therapy such as surgery or bevacizumab administration [23,24]. Human surgical specimens of RN have been shown to exhibit overproduction of VEGF in reactive astrocytes in the perinecrotic area, resulting in leaky angiogenesis with perifocal edema [22]. Bevacizumab would serve to neutralize this overproduced VEGF and subsequently reduce the associated edema [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting edema promotes perilesional hypoxia, driving HIF-1α expression [35] and stimulating a VEGF feedback loop, perpetuating a cycle of edema. Surgical resection of the perinecrotic contrast-enhancing zone in AIRS has been shown to often result in radiographic and clinical improvement [36]; in the case of LITT, the goal of treatment is transformation of the perinecrotic zone into an area of inactive, factor-depleted coagulative necrosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting edema promotes perilesional hypoxia, driving HIF-1α expression [35] and stimulating a VEGF feedback loop, perpetuating a cycle of edema. Surgical resection of the perinecrotic contrast-enhancing zone in AIRS has been shown to often result in radiographic and clinical improvement [36]; in the case of LITT, the goal of treatment is transformation of the perinecrotic zone into an area of inactive, factor-depleted coagulative necrosis [33].In this case, surgical extirpation would have alleviated the mass effect directly, with the additional benefit of offering a histologic diagnosis. However, the lesion was in the superior frontal gyrus, within the supplemental motor area and abutting motor cortex; the associated edema can be seen infiltrating hand motor cortex (Fig.…”
mentioning
confidence: 99%
“…Although classically characterized as an angiogenic factor, VEGF also potentiates capillary permeability [8]. Nonoguchi et al showed overexpression of VEGF in resected radiation necrosis lesions [9]. Furthermore, degree of radiation injury has been correlated with amount of VEGF expression [10].…”
Section: The Role Of Bevacizumab In Treatment For Radiation Necrosis mentioning
confidence: 99%